2022
DOI: 10.1111/ics.12820
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of penetration and permeation of caffeine by confocal Raman spectroscopy in vivo and ex vivo by tape stripping

Abstract: Objective: Tape stripping is an often-used non-invasive destructive method to investigate the skin penetration of a substance. In recent years, however, the suitability of confocal Raman spectroscopy (CRS) as a non-invasive method of nondestructive examination of the skin has become increasingly apparent. In this study, we compared invasion and depletion penetration and permeation kinetics of a 2% caffeine solution with and without 1,2-pentanediol as a penetration enhancer measured with CRS and tape stripping.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although regulatory bodies have not yet adopted the method in their guidelines, research is generating more and more evidence to correlate CRS data to date from conventional methods like tape stripping. For example, Kourbaj et al [ 161 ] and Krombholz et al [ 162 ] showed that the penetration of caffeine and retinol can be monitored by CRS as well as by tape stripping and provide similar results. They described two important advantages of CRS.…”
Section: Methods For Studying Skin Penetration and Formulationsmentioning
confidence: 95%
“…Although regulatory bodies have not yet adopted the method in their guidelines, research is generating more and more evidence to correlate CRS data to date from conventional methods like tape stripping. For example, Kourbaj et al [ 161 ] and Krombholz et al [ 162 ] showed that the penetration of caffeine and retinol can be monitored by CRS as well as by tape stripping and provide similar results. They described two important advantages of CRS.…”
Section: Methods For Studying Skin Penetration and Formulationsmentioning
confidence: 95%
“…This discrepancy might be explained by the higher capability of PCA-LDA to detect CF and PG in the SC. Moreover, it is established that the PG, as a penetration enhancer, can reach the SC bottom and even permeate the SC, while CF 29,30,39]. In addition, it should be taken into consideration that the barrier function of SC in porcine skin ex vivo is lower than in human skin in vivo [86], so we expect that under real in vivo conditions in humans, the penetration depth of CF and PG will be lower.…”
Section: The Maximum Penetration Depthmentioning
confidence: 99%
“…The SC's barrier is more resistant to hydrophilic than to lipophilic substances [28], so transdermal delivery of hydrophilic drugs remains a real challenge. Therefore, a large amount of topically applied hydrophilic CF resides on the skin surface [2] and saturates mainly the outermost SC [29,30]. To solve the problem of permeation through the skin barrier, invasive methods such as microneedling, electroporation, iontophoresis, ultrasound, intradermal injection (including jet injection), and their combination are used to deliver CF into the dermis [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tape-stripping-based lowinvasive ATR-FTIR and EPR spectroscopy methods are commonly used in in vivo skin penetration studies, but require special permission and are severely limited in patients. Low-invasive methods can be applied both in vivo and ex vivo and include tape stripping, primarily applied at the SC [16][17][18]; cyanoacrylate stripping applicable to the SC and viable epidermis [18,19]; suction blister after the application of partial negative pressure on the skin with further analysis of the accumulated interstitial and serum fluids [20]; sampling of the interstitial fluid from the viable epidermis and/or dermis with microneedles [21][22][23] or by microdialysis [24,25], followed by an analysis with validated methods (or their combinations) such as autoradiography for the detection of the radioisotopelabelled penetrants [26], high-performance liquid chromatography, mass spectrometry of various modifications, or UV/VIS spectroscopy (absorption or (epi)fluorescence in a specific spectral range) [26][27][28][29][30]. The skin penetration profile can be determined using low-invasive attenuated total reflectance Fourier-transform infrared (ATR-FTIR) [31][32][33], Fourier-transform infrared photoacoustic spectroscopy (FTIR-PAS) [31], thermal emission decay-Fourier-transform infrared (TED-FTIR) spectroscopy [34], and electron paramagnetic resonance (EPR) spectroscopy [35] for the analysis of the SC removed from skin with tape or cyanoacrylate stripping.…”
Section: Introductionmentioning
confidence: 99%